SYNTACTIC DEPLOYMENTS OF VERB FORMS IN WRITTEN ENGLISH OF FIRST-YEAR STUDENTS OF UNIVERSITY OF AGRICULTURE, MAKURDI - Ambrose Ochigbo , Adaje; Andrew Zakayo, Malata (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The study assesses verb conjugations, usage of verb forms in sentence constructions and syntactic deployments of verb forms in written English of first-year students of University of Agriculture, Makurdi. Structural grammar description of the English verb provides the theoretical framework employed to discriminate wrong verb forms in the students’ works and to develop a competence test, tagged Use of Verb Forms, administered to eighty-four randomized subjects. The results of data analysis, using frequency and percentage, indicate incompetence in verb conjugation, use of verb forms in sentence construction and syntactic deployments of verb forms in sentence structures. On inflections of selected verbs (singe, dye, traffic, bus, bar, call, hoe; lend, shear, bear, mishear, slit, slide, stink), the students could only conjugate one (call). Again, the students are unable to construct sentences with some verb forms(shake, shakes, talked(v-ed2.). On syntactic deployments of verb forms in standard sentences, the base form is used unacceptably in the present tense, the imperative and the present subjunctive structures; the -s form is incorrectly employed in the 3rd person singular present tense context; the -ing participle is unsuitably deployed in the progressive aspect and the -ing participial clause structures; the past form is properly deployed in its past tense structure; the -ed participle is incorrectly deployed in the perfect aspect and the passive structures. Conclusively, the students have difficulty conjugating verbs and using verb forms in English. Undergraduate students should be given required remedial instruction on verb conjugation and functional deployments of verb forms in English for effective communication.